Penerapan Problem Based Learning terhadap Kemampuan Berpikir Kreatif Peserta Didik pada Materi Pengukuran - Sri Latifah; Rita Nur Anjani; Mukarahmah Mustari (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Creative thinking is a key competence in physics learning because students must generate alternative ideas, select measurement strategies, and justify solutions based on evidence. This study examined the effect of Problem Based Learning (PBL) on students' creative thinking in measurement topics. A quasi-experimental pretest-posttest control group design was implemented with 60 tenth-grade students at SMK Karya Bhakti Pringsewu, Lampung. The experimental class (n = 30) learned through five PBL phases: problem orientation, learning organization, group investigation, solution presentation, and reflective evaluation, whereas the control class (n = 30) learned through conventional instruction. Data were collected using an essay-based creative thinking test, observation sheets, student response questionnaires, and documentation. The test measured fluency, flexibility, originality, and elaboration. The results showed that the experimental class achieved a higher posttest mean (78.47) than the control class (64.83). The N-gain of the experimental class was moderate (0.55), whereas the control class was low (0.25). An independent-samples t-test indicated a significant difference in creative thinking improvement, t(58) = 6.91, p < 0.001, with a large effect size (Cohen's d = 1.78). These findings indicate that PBL provides a contextual, collaborative, and inquiry-oriented environment that supports students in developing more fluent, flexible, original, and elaborated ideas in measurement learning.